LIQUIDITY AND CREDIT RISK: A COMPARATIVE STUDY OF ISLAMIC AND CONVENTIONAL BANKS IN INDONESIA - Firdaus, Firdaus; Azlina, Nur; Fakhruddin, Imam; Riyaldi, Rino; Rosman, Romzie (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2024)
Islamic banking is only a small choice for the majority of Indonesian Muslims numbering 229.62 million people or 87.2%. In contrast, the market share of Islamic banks is only 7.07%. Global banking conditions are rocked by the case of Silicon Valley Bank, which is one of the largest banks in the world, experiencing liquidity problems. This is inseparable from the fragility of the conventional banking system based on usury as an inherent obligation. This study analyzes the liquidity and credit risk comparison of Islamic and conventional banks in Indonesia. The sample in this study is 10 Islamic banks and the 10 largest conventional banks in terms of assets in the 2018-2022 period. Independent t-test is used to answer the problems in this study. Based on the results of independent t test show that there is no difference between the liquidity of Islamic and conventional banks. Likewise, NPF / NPL shows no difference between Islamic and conventional banks.